Epistemological Obstacle Of Students In Solving Hots Questions In Terms Of Van Hiele's Theory In Analysis Level - Widi Candika Pakaya; Fattah Hanurawan; Ade Eka Anggraini (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Lack of information regarding mathematical knowledge obtained by students can result in these students experiencing epistemological obstacles. The main goal of this study is to describe the epistemological obstacle faced by students Van Hiele's level of analysis when attempting to solve HOTS Questions. This study uses a qualitative, descriptive methodology. The instruments used are Van Hiele Geometry Test and HOTS questions. Data is collected through interviews and student work. the research subjects were two participants who have reached analysis level according to Van Hiele’s theory in the 4th grade. In this study the data were analyzed by identifying the answers of 2 respondents to the indicators of epistemological barriers that had been done by the students, then interviewing the respondents. The results of this study were students who reached the level of analysis according to Van Hiele's theory encountered epistemological obstacles, such as conceptual, procedural, and operational technical obstacles, for various indicators. The difficulties and obstacles that these students encountered can be used as a guide when creating learning strategies, particularly for the content of geometry.